Analysis Level Smartphone Addiction in Pre Clinic Student at Faculty of Medicine Halu Oleo University - Ibrahim, Fauziah; Halimah; Asia, Sri; Kadek, Ayu; Tosepu, Ramadhan; Effendy, Devi Savitri; Susanty, Sri (Universitas Mandala Waluya, 2023)
One proof of the development of information and communication technology is the creation of smartphones. However, using smartphones has both positive and negative effects. One of the negative impacts of using smartphones, such as smartphone addiction, which has an impact on physical health, also has an impact on psychological and mental health in the form of loneliness, anxiety, stress, depression, life satisfaction, and environmental relations. The purpose of this study was to determine the level of smartphone addiction among pre-clinical students at the Faculty of Medicine, University Halu Oleo Kendari. Research design descriptive. The research was conducted at the Faculty of Medicine, Halu Oleo University, on April 6–11, 2023. The sample was 83 students from the Faculty of Medicine at Halu Oleo University. Sample Obtained using stratified random sampling techniques. Data was obtained using the Smartphone Addiction Scale (SAS) questionnaire. Data processed with SPSS, is displayed in the frequency distribution table. The results of the study found smartphone addiction among students at the Faculty of Medicine, Halu Oleo University, with a low addiction level. The highest number is between 17-19 years. There are more women than men. It was concluded that the level of smartphone addiction among students of the Faculty of Medicine at Halu Oleo University was in the mild category. Most occurrences are in women, aged 17–19 years. Influence factors of smartphone addiction include a high desire to explore new things in information and technology.